The first southern hemisphere occurrence of the extinct Cretaceous sclerorhynchoid sawfish Ptychotrygon (Chondrichthyes, Batoidea), with a review of Ptychotrygon taxonomy. Issue 2 (31st August 2022) - Begat, Arnaud; Kriwet, Jürgen; Gelfo, Javier N.; Cavalli, Soledad Gouiric; Schultz, Julia A.; Martin, Thomas
ABSTRACT: A new extinct sclerorhynchoid sawfish, Ptychotrygon ameghinorum sp. nov., is presented here based on abundant isolated teeth and some dermal denticles, which were recovered from the Mata Amarilla Formation, belonging to the lower Upper Cretaceous of the Santa Cruz Province in the Austral Basin of Patagonia, Argentina. This new species is the first Ptychotrygon occurrence in the southern hemisphere, which so far only has been reported from northern hemisphere deposits (Europe, North Africa, and North America). The presence of P. ameghinorum sp. nov. in these southern high-latitude deposits of Patagonia, Argentina, extends the geographic range of Ptychotrygon considerably southwards. This distribution pattern in the "middle" Cretaceous seems to correlate with the South Atlantic opening at the end of the Albian. The presence of lateral cephalic dermal denticles and the simultaneous absence of rostral denticles in the abundant fossil material support the view that Ptychotrygon did not develop such rostral structures. A reinvestigation of all known species assigned to Ptychotrygon reveals that P. ellae is a junior synonym of P. boothi, P. benningensis belongs to Texatrygon, P. rugosum belongs to Asflapristis, and P. clementsi represents an unidentifiable species ( Ptychotrygon ? sp.). The stratigraphic distribution demonstrates that Ptychotrygon might have originated in the Albian in south-western Europe and subsequently dispersed to obtain its widest distribution during the Cenomanian. In the Coniacian, a steep diversity decline is recognizable with a subsequent distribution shift from Europe to North America.